Automatic Delirium Prediction System and Nursing-Sensitive Outcomes in the Medical Intensive Care Unit. (February 2015) - Cho, Ha-young; Song, Xianghua; Piao, Jinshi; Jin, Yinji; Lee, Sun-Mi
In Korea, delirium risk screening has not been routinely implemented in intensive care units (ICUs). The purpose of this study was to implement an Automatic Prediction of Delirium in Intensive Care Units (APREDEL-ICU) system to investigate its impact on nursing-sensitive outcomes and to assess nurse satisfaction with the system. A pre–post research design was used. A total of 145 patients were involved prior to the system implementation and 172 were involved after implementation. Forty medical ICU nurses evaluated the system. The APREDEL-ICU system did not result in a reduction in the incidence of delirium. However, the nurses reported that their knowledge regarding delirium care increased after the system was introduced. The proposed system was successfully implemented without increasing the burden of nurses in their assessment of delirium risk. Long-term use of APREDEL-ICU could enhance preventive care and consequently result in positive patient outcomes.